Analisis Wake Area Desain Mobil Box dengan Simulasi Aerodinamika - Edwin Sahrial Solih; Sanurya Putri Purbaningrum; Abdul Wahid Arohman; Hendi Lilih Wijayanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The standard box car design has a large drag and wake area which results in high fuel consumption. One way to reduce drag and wake area is to modify the box car design. Modifications were made by adding an aerokit spoiler and deflector to a standard box car which is expected to reduce drag and wake areas. The next step is to design a simulation using CFD-based CAD. The analysis was carried out with three variations of speed, namely 60 km/hour, 80 km/hour and 100 km/hour. The simulation results show that the design of the box car with the modification of the addition of aerokit spoilers and deflectors can reduce the drag and wake areas.